Geomagnetic Activity at Lampedusa Island: Characterization and Comparison with the Other Italian Observatories, Also in Response to Space Weather Events - Domenico Di Mauro; Mauro Regi; Stefania Lepidi; Alfredo Del Corpo; Guido Dominici; Paolo Bagiacchi; Giovanni Benedetti; Lili Cafarella (Remote Sensing, 2021)
Regular automatic recordings of the time series of the magnetic field, together with routine manual absolute measurements for establishing dynamic baselines at Lampedusa Island—south of Sicily—Italy (geographic coordinates 35°31′N; 12°32′E, altitude 33 m a.s.l.), show a signature of very low electromagnetic noise. The observatory (provisional IAGA code: LMP) lays inside a restricted and remote wildlife reserve, far away from the built-up and active areas of the island, which at present is the southernmost location of the European territory for such observations. The availability of high-quality data from such site, whose survey started in 2005, is valuable for filling the spatial gap due to the lack of observatories in the whole south Mediterranean and North African sectors. We compare observations at Lampedusa, in both time and frequency domains, with those at the other Italian observatories (Castello Tesino and Duronia-L’Aquila), operating since the 1960s of last century, allowing us to report even the secular variation. Using data recorded in the last few years, we investigate higher frequency variations (from diurnal to Pc3-4 pulsations) in order to magnetically characterize the Italian territory and the local response to external forcing. In particular, we present a characterization in terms of diurnal variation and its seasonal dependence for the three observatories. This latter feature is in good agreement with a geomagnetic Sq-model, leading us to speculate about the position of the north Sq-current system vortex and its seasonal displacement with respect to the geographic positions of the observatories. We also study the geomagnetic individual response to intense space weather events by performing Superposed Epoch Analysis (SEA), with an ad-hoc significance test. Magnetic responses in the Ultra Low Frequency range (ULF) from spectral, local Signal-to-Noise Ratio (SNR) analyses under different local time, and polarization rates are computed. These latter studies lead us to search for possible signatures of magnetic field line resonances during intense space weather events, using cross-phase multi-observatory analysis, revealing the promising detection capability of such technique even at low latitudes. The geomagnetic observatories prove to be important points of observation for space weather events occurring at different spatial and time scales, originating in both upstream and ionospheric regions, here analyzed by several well-established methodologies and techniques. The quiet environmental site of LMP, providing high-quality geomagnetic data, allows us such investigations even at inner Earth’s magnetospheric shell.